1985
DOI: 10.1111/j.1502-3931.1985.tb00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Infaunal or semi‐infaunal bellerophont gastropods: analysis of Euphemites and functionally related taxa

Abstract: 198501 15: Infaunal or semi-infaunal bellerophont gastropods:LETHAIA analysis of euphemites and functionally related taxa. Lethaia, Vol. 18, Oslo. ISSN 0024- 1164.Burrowing and plowing gastropods may have existed prior to the Mesozoic, contrary to the conservative tendency of categorizing Paleozoic archaeogastropods as herbivorous hardground dwellers. We propose that Euphemites and other bellerophontiform molluscs such as Praematuratroph and Beyrichidiscus make functional and paleoecological sense only if reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
5
1
2
Order By: Relevance
“…Previous paleoecological interpretations of other Paleozoic gastropods based on the ecology of extant forms has resulted in the oversimplification of their mode of life (Harper and Rollins, 1985). Many Paleozoic gastropods, similar to the taxa in the present study, are found in dark, fine-grained sediments, which contradicts modern analogs that indicate non-predatory gastropods are strictly herbivores limited to clear water environments with firm substrates (Peel, 1978).…”
Section: Biofaciescontrasting
confidence: 85%
See 2 more Smart Citations
“…Previous paleoecological interpretations of other Paleozoic gastropods based on the ecology of extant forms has resulted in the oversimplification of their mode of life (Harper and Rollins, 1985). Many Paleozoic gastropods, similar to the taxa in the present study, are found in dark, fine-grained sediments, which contradicts modern analogs that indicate non-predatory gastropods are strictly herbivores limited to clear water environments with firm substrates (Peel, 1978).…”
Section: Biofaciescontrasting
confidence: 85%
“…Paleoecological aspects of Paleozoic gastropods are not well understood (Aigen, 1974;Harper and Rollins, 1985;Anderson, 1986). In the present study gastropod guilds were based on shell morphology, with the exception of the bellerophontid gastropods, where interpretations of the mode of life of these planispiral gastropods do exist (e.g., Harper and Rollins, 1985).…”
Section: Guild Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…). The best candidates for an infaunal habit in bellerophontoideans are species in such genera as Hispanosinuites , Praematuropsis and Euphemites , in which the shell is partially enveloped by either the mantle or the foot (Harper & Rollins ). Their shells, however, are globose, and not streamlined; and the inductural deposits laid down by the enveloping organ are sculptured.…”
Section: Discussionmentioning
confidence: 99%
“…Autecology. -Linsley (1978) and Harper & Rollins (1985) reconstructed Euphemites with nearly the whole shell covered by tissue. It was interpreted as an active, probably burrowing, predator.…”
Section: Bellerophontoideamentioning
confidence: 99%